094 A Systematic Review of Monogenic Mutations Responsible of Sertoli Cell-Only Syndrome. (1st May 2022) - Bibi, A; Irfan, M; Ishaq, B; Inam, M; Hussain, NHN; Ismail, SB
ABSTRACT: Introduction: Sertoli-cell only syndrome (SCOS) is the severe form of non-obstructive azoospermia, in which only the Sertoli cells line the wall of seminiferous tubules. Y chromosome microdeletions are the obvious cause of SCOS in men, but conclusive and summarized data is lacking on the monogenic mutations. Objective: To systematically review published data on monogenic mutations causing SCOS. Methods: Medline was searched without publication date restriction for all the genetic association studies on SCOS by using keywords: genetics of Sertoli cell-only syndrome, genetics of azoospermia secondary to SCOS and, genes of Sertoli cell-only syndrome. Quality evaluation and data extraction were done by two authors Studies included in the systematic review were presenting original clinical data, human male cases and patients with confirmed SCOS by histopathology or MD-TESE. The genetic evidence of SCOS was included even if the reported case and genetic testing were published separately. Non-English language studies, descriptive reviews, articles of gene expression in SCOS, and articles related to the other chromosomal abnormalities as a cause of SCOS were also excluded. Any dispute on exclusion and inclusion of a study was resolved by discussion and consensus between all authors. Results: The initial database search identified 489 articles, after evaluation according to the defined criteria, only 15 studies matched the inclusion criteria for systematic review. Articles included in the systematic review were published from 2005 to 2020. Only 13% (n=2) of articles were published before 2012. From 2012 to 2020, there have been 87% (n=13) publications. Most of the studies (66.7%, n=10) were carried out on Asian populations (Japanese population) and the rest were on Caucasians. The 15 publications included a total of 1513 cases of SCOS, originating from 7 different countries. However, 151 cases appeared in 2 articles. Extracted data show that 40% of studies exclude patients with a history of infections, seminal tract obstruction, pituitary gland disorder or any other cause of testicular damage, and 27% of studies only recruit patients with no chromosomal abnormalities. Approximately 13% of eligible studies exclude the patients based on congenital abnormalities, past cryptorchidism, orchitis, cancer and other systemic illnesses. In addition, 13% of studies included patients who were diagnosed with SCOS. Only 7% of studies include the patient with unknown cause of male infertility. In all the studies only patients with normal karyotype and without Y-chromosome microdeletions were included. In all the studies semen analysis and confirmatory tests MD-TESE or histopathology were for SCOS. Most of the studies used the technique of direct sequencing and only one study performed whole-exome sequencing. Altogether approximately 51 variations in 13 genes ( USP26, RAD21L, SEPTIN12, PAPOLB, PLK4, H3t, ETV5, GILZ, SIN3A, CUL4B, DMRT1, SPATA17 and, LRWD1) were identified from which only 7 variations showed a statistically significant association, but others showed rare or no association. Conclusion: Comprehensive large-scale studies on monogenic causes of SCOS still lacking. Altogether approximately 51 variations in 13 genes were identified from which only 7 variations showed statistically significant association. Further studies are required to determine the monogenic causes of SCOS. Disclosure: Work supported by industry: no.